Experiences of health care providers on pregnancy and childbirth care during the COVID-19 pandemic in Iran: a phenomenological study - Hantoushzadeh, Sedigheh; Bagheri, Maryam; Amjadi, Marjan Akhavan; Farahani, Maryam Farmahini; Haghollahi, Fedyeh (BMC Pregnancy and Childbirth, 2021)
Coronavirus currently cause a lot of pressure on the health system. Accordingly, many changes occurred in the way of providing health care, including pregnancy and childbirth care. To our knowledge, no studies on experiences of maternity care Providers during the COVID-19 Pandemic have been published in Iran. We aimed to discover their experiences on pregnancy and childbirth care during the current COVID-19 pandemic. This study was a qualitative research performed with a descriptive phenomenological approach. The used sampling method was purposive sampling by taking the maximum variation possible into account, which continued until data saturation. Accordingly, in-depth and semi-structured interviews were conducted by including 12 participants, as 4 gynecologists, 6 midwives working in the hospitals and private offices, and 2 midwives working in the health centers. Data were analyzed using Colaizzi’s seven stage method with MAXQDA10 software. Data analysis led to the extraction of 3 themes, 9 categories, and 25 subcategories. The themes were as follows: “Fear of Disease”, “Burnout”, and Maternal health care providers experience emotional and psychological stress and work challenges during the current COVID-19 pandemic. Therefore, comprehensive support should be provided for the protection of their physical and mental health statuses. By working as a team, utilizing the capacity of telemedicine to care and follow up mothers, and providing maternity care at home, some emerged challenges to maternal care services can be overcome.